Local Self-government and Out-of-school Education in the Russian Empire During the First World War - Pokotilova, Tatyana Evgenevna; Rusetskiy, Mikhail Gennad’evich; Samylov, Pavel Vasilyevich; Miroshnichenko, Nadezhda Viktorovna; Kochkarova, Zarema Ruslanovna (Journal of History Culture and Art Research, 2018)
The article is devoted to the analysis of the actions of such a body of local self-government in pre-revolutionary Russia as zemstvo in organization of the cultural growth of the rural population of Stavropol province on the eve and in the early years of the First World War. The authors, depending on the basic principles and methods of historical research, have revealed and investigated the main forms and results of out-of-school education organized and supported by the zemstvo of Stavropol province within the existing powers, financial possibilities and wartime conditions. The results suggest that the highest interest, activity and success of zemstvo lecturers in educating fellow countrymen continue before and, even, during the First World War. Moreover, such activity broke the stereotypes of the hostile attitude of part of the Stavropol peasantry to a new form of management as zemstvo, and enabled to gradually establish in the region an algorithm of the organization and functioning of a local government system adequate to the needs of Russia in the beginning of the twentieth century.